Calculation of cams with concave profile in the MATHCAD system - V. V. Ryndin; Yu. P. Makushev; T. A. Polyakova; L. Yu. Volkova (Омский научный вестник)
The article shows the features of the cam with concave profile, the method of kinematic calculation of the pusher when it moves along a concave and rounded surface. The formula for determining the magnitude of the pusher velocity on the concave surface of the cam is refined. A method for determining the coordinate center for the radius of the concave surface of the cam is proposed. To increase the speed of the plunger and intensify the fuel injection process in high-pressure pumps of lowspeed diesel engines, it is recommended to use cams with concave profile. The calculation is performed using the Mathcad system of the stroke, speed and acceleration of the pusher depending on the angle of rotation of the cam shaft. Using the Mathcad program for cams with a concave profile, graphs of the pusher lift, changes in its speed and acceleration are constructed.